Employee Engagement in Digital Logistics: The Effect of Human Capital Management, Culture, and Technology Acceptance - Furqon Mazka; Haryadi; Idham Khalik; Sry Rosita; Syahmardi Yacob (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The problem addressed concerns the limited integration of human and organizational factors in supporting digital transformation, which may affect employee engagement in technology-intensive environments. This study examines the influence of human capital management and organizational culture on employee engagement, with technology acceptance serving as a mediating variable in the logistics industry. This study employed a quantitative research design. Data were collected through a survey of 265 employees at an Indonesian logistics company, and Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the direct and indirect relationships among the variables. Results indicate that human capital management and organizational culture each exert a positive and significant effect on employee engagement. Moreover, technology acceptance significantly mediates these relationships and emerges as the most influential determinant of employee engagement. The findings highlight that employees’ perceptions of usefulness and ease of use of digital systems play a critical role in enhancing engagement. Organizations in the logistics sector are therefore advised to integrate human capital development, adaptive organizational culture, and user-oriented digital systems in order to sustain employee engagement throughout the digital transformation process.